Influencing Factors The Works Discipline of Employees Mercure Hotel Bengkulu City - Tiopani, Deby Elsa; Yanti, Rina Trisna; Effendi, Yanto (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This research aims to find out the factors influencing the work discipline of employees at the Mercure Hotel, Bengkulu City. Methodology: This type of research is descriptive analysis. The sampling method uses the census method, where part of the population is sampled. The data collection method in this research uses a quantitative method which is carried out by distributing questionnaires. opinions and perceptions given by respondents using a Likert scale. The analytical method used is rating scale analysis.. Results : it is proven that the factors that influence employee work discipline include indicators of motivation, education and training, leadership and welfare. The leadership factor is the most dominant factor influencing employee work discipline. Findings: at the Mercure Hotel, Bengkulu City, we found that the lowest factor was education and training. It would be best to provide discipline training for employees so that they can improve their performance in the future. Novelty and Originality: This research contributes to improving human resources in improving organizational performance. Conclusion: factors that influence employee work discipline from indicators of motivation, education and training, leadership and welfare at the Mercure Bengkulucity. The leadership factor is the most dominant factor influencing employee work discipline at the Mercure Bengkulu . Type of Paper: riset paper